Dvodimenzionalno modeliranje toka s prosto gladino - Četina, Matjaž (Acta hydrotechnica, 2000)
Some theoretical background of the two-dimensional (2D) depth-averaged mathematical models PCFLOW2D and PCFLOW2D-Curve is described first. Basic equations of continuity, momentum conservation and the transport of turbulent kinetic energy per unit mass and its rate of dissipation are solved by using the finite volume numerical method. Several practical flow computations are shown: a steady flow in the Idrijca River narrow, a 2D flow of the Savinja River in the city of Laško and an unsteady dam-break flow in the sudden expansion and tidal flow in the system of three Mexican Pacific lagoons - Jitzamuri, Agiabampo and Bacorehuis. The comparison between the computed results and the field measurements or the physical models showed satisfactory agreement
Keywords: curvilinear coordinates; dam-break wave; depth-averaged model; dvodimenzijsko matematično modeliranje; globinsko povprečni model; Idrijca River narrow; krivočrtne koordinate; Laško; mehiške lagune; Mexican lagoons; ožina Idrijce; porušitveni val; Savinja; two-dimensional modelling